How the British Cycling Team dominated using Big Data - Hill, G. (Sports Performance & Tech, 2016)
During the Rio Olympics, the British cycling team had huge success. On the road, they picked up a bronze in the Mens Time Trial, with Chris Froome finishing behind Thomas Demoulin and Fabian Cancellara, however, it was in track cycling where they really dominated, with the team taking home 11 medals from a possible 30. They managed to win 6 golds out of a possible 10, and of the 4 where they didn't win gold, one they didn't enter a team and the other three they came second.